Literasi keuangan dan strategi manajemen digital bank syariah dalam meningkatkan adopsi layanan oleh generasi z - Agustiawan, Muhammad Iqbal (Maliki Interdisciplinary Journal, 2025)
The development of digital technology following the pandemic has brought significant changes to the working systems of financial institutions, including Islamic banks. Service processes have shifted entirely to digital, making them more efficient and accessible to the public. However, this change also presents new challenges, particularly for Generation Z, who are the primary users of digital services but still have low levels of Islamic financial literacy. According to a 2024 OJK survey, the Islamic financial literacy rate among Gen Z has only reached 19.4%, while the inclusion rate has exceeded 80%. This situation highlights the need for a digital management strategy that focuses not only on technological development but also on improving customer understanding of Islamic financial principles. This article uses a literature review method that reviews various studies on Islamic financial literacy, Gen Z financial behavior, and Islamic banking digital management strategies. The study results indicate that Islamic financial literacy plays a crucial role in increasing Generation Z's trust and interest in digital Islamic banking services. Conversely, innovative digital management strategies help banks deliver modern services while remaining compliant with Islamic values. The two are interrelated and are key to the success of Islamic banking in increasing the adoption of digital services in the era of technological transformation.